Single-dose Intramuscular Toxicity of Neutral Natured Blood Stasis Pharmacopuncture in Sprague-Dawley Rats - In Ho Yeo; Eun Yong Lee (Korean Pharmacopuncture Institute, 2014)
Objectives:This study was performed to analyze the single-dose toxicity of neutral natured blood stasis pharmacopuncture extracts. Methods:All experiments were conducted at Biotoxtech, an institution authorized to perform non-clinical studies, under the regulations of Good Laboratory Practice (GLP). Sprague-Dawley rats were chosen for the pilot study. Doses of neutral natured blood stasis pharmacopuncture extracts, 0.1, 0.5 and 1.0 mL, were administered to the experimental group, and the same doses of normal saline solution were administered to the control group. This study was conducted under the approval of the Institutional Animal Ethics Committee. Results:In all 4 groups, no deaths occurred, and the neutral natured blood stasis pharmacopuncture extracts administered by intramuscular (IM) injection was over 1.0 mL/animal. No significant changes in the body weights between the control group and the experimental group were observed. To check for abnormalities in organs and tissues, we used microscopy to examine representative histological sections of each specified organ; the results showed no significant differences in any organs or tissues. Conclusion:The above findings suggest that treatment with neutral natured blood stasis pharmacopuncture extracts is relatively safe. Further studies on this subject should be conducted to yield more concrete evidence.